1998
DOI: 10.1002/(sici)1099-1379(199805)19:3<305::aid-job843>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Explaining nursing turnover intent: job satisfaction, pay satisfaction, or organizational commitment?

Abstract: SummaryA number of models have been developed to explain nurses' turnover behavior. The common theme that emerges from these models is that turnover behavior is a multistage process that includes attitudinal, decisional, and behavioral components. The purpose of this study was to assess both the direct and indirect impact of certain pay policies upon the turnover intentions of paediatric nurses. The two major questions addressed were: What was the relative impact of job satisfaction, pay satisfaction, and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
369
4
44

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(458 citation statements)
references
References 39 publications
31
369
4
44
Order By: Relevance
“…Hasil penelitian ini sejalan dengan penelitian Lum, et al (1998) Hipotesis keempat menyatakan employee engagement memiliki pengaruh tidak langsung terhadap turnover intention melalui kepuasan kerja di RS Wava Husada Kepanjen terbukti dalam penelitian ini. Employee engagement berpengaruh terhadap kepuasan kerja dan kepuasan kerja berpengaruh terhadap turnover intention, maka employee engagement berpengaruh terhadap turnover intention melalui kepuasan kerja sehingga dapat disimpulkan bahwa data penelitian mendukung hipotesis ini.…”
Section: Pembahasanunclassified
“…Hasil penelitian ini sejalan dengan penelitian Lum, et al (1998) Hipotesis keempat menyatakan employee engagement memiliki pengaruh tidak langsung terhadap turnover intention melalui kepuasan kerja di RS Wava Husada Kepanjen terbukti dalam penelitian ini. Employee engagement berpengaruh terhadap kepuasan kerja dan kepuasan kerja berpengaruh terhadap turnover intention, maka employee engagement berpengaruh terhadap turnover intention melalui kepuasan kerja sehingga dapat disimpulkan bahwa data penelitian mendukung hipotesis ini.…”
Section: Pembahasanunclassified
“…Tett and Meyer (1993) found that job satisfaction was a strong predictor of intention to quit. Lum, Kervin, Clark, Reid, and Sirola (1998) found that job satisfaction had an indirect relationship on intention to quit, whereas commitment had a direct effect on intention to quit. Based on the hope-satisfaction link and research linking satisfaction to turnover intentions, it may follow that Indian BPO workers who are more hopeful will have more job satisfaction and demonstrate less interest in leaving the organization.…”
Section: The Relevance Of Hope For the Indian Bpo Sectormentioning
confidence: 99%
“…Turnover has various results such as increasing the cost of employing staff, diminishing the organization's knowledge capital and damaging its reputation (Liu et al, 2010, Lum et al, 1998. As Moynihan and Pandey (2007) have stated, there are three categories of factors that affect turnover intention.…”
Section: Introductionmentioning
confidence: 99%